Right Heart Thrombi: Patient Outcomes by Treatment Modality and Predictors of Mortality: A Pooled Analysis. (November 2019) - Islam, Marjan; Nesheim, David; Acquah, Samuel; Kory, Pierre; Kourouni, Ismini; Ramesh, Navitha; Ehrlich, Madeline; Bajpayee, Gargi; Steiger, David; Filopei, Jason
Rationale: Right heart thrombi (RiHT) is characterized by the presence of thrombus within the right atrium or right ventricle (RV). Current literature suggests pulmonary embolism (PE) with RiHT carries a high mortality. Guidelines lack recommendations in managing RiHT. We created a pooled analysis on RiHT and report on our institutional experience in managing RiHT. We aimed to evaluate whether patient characteristics and differing treatment modalities predict mortality. Methods: We created a pooled analysis of case reports and series of patients with RiHT and PE between January 1956 and 2017. We also reviewed a series of consecutive patients with RiHT identified from our institutional PE registry. Age, shock, RV dysfunction, clot mobility, treatment modality, and hospital outcome had to be reported. Results: We identified 316 patients in our pooled analysis. Patients received the following therapies: no treatment 15 (5%), systemic anticoagulation 73 (23%), systemic thrombolysis 108 (34%), surgical embolectomy 101 (32%), catheter-directed therapy 11 (3%), and systemic thrombolysis with surgery 8 (3%). In-hospital mortality was 18.7%. Univariate analysis showed age and shock reduced odds of survival. Multivariate analysis showed shock reduced odds of survival (odds ratios [OR] 0.36, 95% confidence interval [CI]: 0.19-0.72, P ≤ .01) while age, RV dysfunction, and clot-mobility did not affect mortality. In a reduced multivariate analysis adjusting for shock, treatment modality, and clot location alone, systemic thrombolysis increased odds of survival when compared to systemic anticoagulation (OR 2.72, 95% CI: 1.11-6.64, P = .02). Our institutional series identified 18 patients, where in-hospital mortality was 22.2%, 18 (100%) had RV dysfunction, and 5 (28%) had shock. Patients received the following therapies: systemic anticoagulation 8 (44.4%), systemic thrombolysis 4 (22.2%), surgical embolectomy 4 (22.2%), and catheter-directed thrombolysis 2 (11.1%). Conclusion: Presence of shock in RiHT is an independent predictor of mortality. Systemic thrombolysis may offer increased odds of survival when compared to systemic anticoagulation. Our findings should be interpreted with caution as they derive from retrospective reports and subject to publication bias.